Expecting Surprise Again: Neil Young and the Dialogic Theory of Genre - Echard, William (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2002)
This paper has two aims: (i) to develop a dialogic theory of genre and stylistic reference, especially but not exclusively for application to rock music; and (ii) to offer a detailed reading of genre play and associated issues—instability, authenticity, and unpredictability—in the music of Neil Young. Under this approach authors, performers, styles, and genres are all treated as various forms of persona, allowing for a fully dialogic analysis of their relationships and mutual interpenetrations.